Volkman’s Contracture, Persistent Limb Ischaemia, and Amputation: A Complication of Brachial Artery Catheterisation for Haemodynamic Monitoring Using PiCCO - Veejay Bagga; Marion Palmer; Ramesh Sadasivan; Govindan Raghuraman (Case Reports in Critical Care)
We report a case of a 64-year-old woman who was admitted to intensive care unit with multiorgan failure secondary to Plasmodium falciparum malaria. Haemodynamic monitoring using the transpulmonary thermodilution with pulse contour analysis system (PiCCO) was achieved via the left brachial artery. Two days later, a flexion deformity of the left hand was noted, and examination revealed left lower arm ischaemia. Removal of the catheter resulted in an immediate improvement of the contracture. However, distal pulses were still absent, and the arm remained ischaemic resulting in a below elbow amputation. This is the first documented case of a persistent limb ischaemia following the insertion of an arterial catheter for haemodynamic monitoring with PiCCO. We therefore highlight the need for regular assessment of limb perfusion after arterial catheterisation for haemodynamic monitoring with PiCCO. In addition, the brachial artery should be avoided, and femoral artery catheterisation is recommended.